The spiritual needs of surgical patients in Iranian hospital settings: a qualitative study - Fahimeh Alsadat Hosseini; Marzieh Momennasab; Shahrzad Yektatalab; Armin Zareiyan (BMC Research Notes)
Abstract Background and aim Surgical patients seek spiritual support because they feel threatened by their physical integrity and sense of self. Delivering spiritual care to surgical patients requires recognizing their spiritual needs. These needs can take on various forms in different cultures and religions. Thus, the present study aimed to investigate the spiritual needs of surgical patients in Iranian hospital setting. Method This qualitative content analysis study research was conducted on 16 surgical hospitalized patients in Shiraz, Iran. The data was collected through in-depth and semi-structured interviews. The qualitative content analysis method of Graneheim and Lundman was used for analyzing the data, and Guba and Lincoln criteria were used to ensure the trustworthiness of the research data. Results The findings of this study were presented in the form of four key categories: “Divine Resilience,” which highlights the need for a divine relationship to achieve spiritual strength; “Supportive Bonds in the Healing Process,” emphasizing the importance of interpersonal connections and support networks; “Peaceful Environment,” reflecting the necessity of a tranquil and supportive setting; and “Transcendence Beyond Difficulties,” which underscores the patients’ quest for meaning and purpose amidst their challenges. Conclusion Surgical patients experience interconnected spiritual needs, including divine resilience, supportive interpersonal relationships, a peaceful environment, and transcendence beyond difficulties. Addressing these needs by healthcare authorities and policymakers is essential for providing holistic surgical care and enhancing patients’ overall well-being.